2019
DOI: 10.1097/dad.0000000000001261
|View full text |Cite
|
Sign up to set email alerts
|

Facial Phaeohyphomycosis in an Immunocompetent Individual: A Rare Presentation of a Rare Fungus

Abstract: Phaeohyphomycosis is a rare mycotic infection caused by heterogenous groups of dematiaceous fungi involving the skin and subcutaneous tissue. Here, we report a case of cutaneous phaeohyphomycosis presenting as cauliflower-like verrucous lesion over the face in an immunocompetent individual. Histopathology showed suppurative granulomatous inflammation replete with pigmented broad fungal hyphae which is stained with periodic acid–Schiff stain, Grocott's methanamine silver stain, Schmorl's stain, and Masson-Fonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…In the recent decade, an upsurge in the incidence rate of rarely encountered dematiaceous fungal agents causing opportunistic infections has been observed. Several case reports of cutaneous phaeohyphomycosis caused by various dematiaceous fungi, such as Exophiala , Curvularia , Cladosporium , Alternaria and Fonsecaea have been reported from India and some other countries 9,11,32–37 . Similar to our results, a case of cutaneous phaeohyphomycosis of foot web by Curvularia lunata in a 31‐year‐old immunocompetent male has been reported 38 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the recent decade, an upsurge in the incidence rate of rarely encountered dematiaceous fungal agents causing opportunistic infections has been observed. Several case reports of cutaneous phaeohyphomycosis caused by various dematiaceous fungi, such as Exophiala , Curvularia , Cladosporium , Alternaria and Fonsecaea have been reported from India and some other countries 9,11,32–37 . Similar to our results, a case of cutaneous phaeohyphomycosis of foot web by Curvularia lunata in a 31‐year‐old immunocompetent male has been reported 38 .…”
Section: Discussionsupporting
confidence: 89%
“…Several case reports of cutaneous phaeohyphomycosis caused by various dematiaceous fungi, such as Exophiala, Curvularia, Cladosporium, Alternaria and Fonsecaea have been reported from India and some other countries. 9,11,[32][33][34][35][36][37] Similar to our results, a case of cutaneous phaeohyphomycosis of foot web by Curvularia lunata in a 31-year-old immunocompetent male has been reported. 38 Another recent case study from Brazil reported Exophiala xenobiotica as an etiological agent of cutaneous phaeohyphomycosis in a 45 years old man.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Various dematiaceous fungi have been reported from phaeohyphomycotic cysts. Various unusual fungal agents such as Phialemoniopsis ocularis [10], Phaeoacremonium inflatipes [11], Exophiala oligosperma [12], Exophiala spinifera [13], Medicopsis romeroi (Pyrenochaeta romeroi) [14,15] are the reported from of subcutaneous phaeohyphomycosis.…”
Section: Discussionmentioning
confidence: 99%